2020
DOI: 10.3126/gjn.v13i0.28153
|View full text |Cite
|
Sign up to set email alerts
|

Women in foreign employment: Its impact on the left behind family members in Tanahun district, Nepal

Abstract: Though, the migration process and its impact in the household economy has been extensively studied in the academic sectors, but much less attention has been given to the impact of female labor migration on the family members who are left behind at home. This paper attempts to determine socio-economic structure of female labor migrants from Tanahun District of Gandaki Province, Nepal. Similarly, it also attempts to analyze the causes of female migration, process and dynamics of foreign labor migration and its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…However, this result different from national reports (MOLESS, 2020) which mentioned Kuwait is one of the major destination but not the top country for migration. However, a study in Tanahun Nepal reported Kuwait was among the top three countries preferred by women migration without significant difference among the top three destination countries (Sapkota, 2020). This may be due to an understanding of little or limited awareness and education regarding foreign labour migration.…”
Section: Destination For Labor Migrationmentioning
confidence: 96%
See 1 more Smart Citation
“…However, this result different from national reports (MOLESS, 2020) which mentioned Kuwait is one of the major destination but not the top country for migration. However, a study in Tanahun Nepal reported Kuwait was among the top three countries preferred by women migration without significant difference among the top three destination countries (Sapkota, 2020). This may be due to an understanding of little or limited awareness and education regarding foreign labour migration.…”
Section: Destination For Labor Migrationmentioning
confidence: 96%
“…Similarly, Sijapati et al (2019) studied on the policy and regulatory frameworks of Nepal related to female labour migration indicated working conditions abroad are not affected by sending country policies. A recent study by Sapkota (2020) on International female labour migration and its impact on the left behind family members in their home in the Tanhun district of Nepal and considered more work required in this aspect. Against this backdrop, this article attempts to analyse changes in gender roles and impact on women family members as well as the attitudes towards women migration.…”
Section: Introductionmentioning
confidence: 99%
“…Many migrating persons to cities and abroad leave their wives, children, and elderly parents. The movement of the people from rural to urban areas represents a significant livelihood strategy for the poor to maximize family income and minimize the environmental risk (Adger et al, 2015;IOM & Save the Children, 2017;Sapkota, 2020;Singh, 2019). Similarly, Sapkota (2018) claims that 62 percent of rural households migrate for work to earn more and have better livelihoods and the other 20 percent migrate because they are only employed seasonally at their native place and the rest want to save money for the social and cultural obligation.…”
Section: Change In the Family's Livelihood And Land Managementmentioning
confidence: 99%
“…There is very little literature available on the impact of female migration to the left behind families, especially concerning the children. The recent study by Sapkota (2020) reveals that left-behind children face numerous adverse effects of female migration including problems related to the caring deficit, psychological problem, health, education, aggressive behavior, physical abuse and anti-social activities due to the lack of motivation from others at home but the positive side is the alleviation of poverty, improvement of education quality improvement, improve lifestyle, and health care services. Despite the high level of parental international labor migration from Nepal, Kunwar et al (2020) find that children of migrants had a similar level of health care seeking and nutritional status to children of non-migrants because of the improved household economic condition by remittance and less migration number of mothers.…”
Section: Impact Of Migration On the Left-behind Children's Health And Caretakermentioning
confidence: 99%
“…According to Islam et al (2019), remittances from parental migration give families more purchasing power for food and health care, which may aid in child nutritional development but harm psychological development because parents do not provide direct care to their children. Furthermore, Sapkota (2020) adds that left-behind children from migrant families face a variety of negative consequences, including issues related to the caring deficit, psychological problems, health, education, violent behavior, physical abuse, and anti-social activities due to a lack of encouragement from others at home, but the positive aspects include poverty alleviation, education quality improvement, better lifestyle, and access to health care services.…”
Section: Introductionmentioning
confidence: 99%